Los límites del odio : la compasión de Odiseo en âAyax de Sófocles (2017)
Pity plays a major role in ancient Greek tragedy, as Aristotle himself recognized. But, regardless of what the Stagirite said, it is possible for us to see the importance of this emotion in the plays of the main Greek tragedians: Aeschylus, Sophocles and Euripides. In the present work, I will study the notion of compassion that underlies Sophocles? play Aias in order to show, in a case study, that the Greek notion of pity depends on a series of cognitive conditions that Aristotle already recognized in his treaty on Rhetoric. By doing this, I will show the relationship between pity and certain notions of justice present in the contrasts that Sophocles creates between the different characters of his play, these contrasts take place in virtue of the emotions and beliefs that each one of the characters feels and holds. With this analysis, I want to contribute to an independent study of Sophocles works from a philosophical perspective.